Performance Enhancement of APW+lo Calculations by Simplest Separation of Concerns - Long Zhang; Anton Kozhevnikov; Thomas Schulthess; Hai-Ping Cheng; Samuel B. Trickey (Computation, 2022)
Full-potential linearized augmented plane wave (LAPW) and APW plus local orbital (APW+<semantics>lo</semantics>) codes differ widely in both their user interfaces and in capabilities for calculations and analysis beyond their common central task of all-electron solution of the Kohn–Sham equations. However, that common central task opens a possible route to performance enhancement, namely to offload the basic LAPW/APW+<semantics>lo</semantics> algorithms to a library optimized purely for that purpose. To explore that opportunity, we have interfaced the Exciting-Plus (“EP”) LAPW/APW+<semantics>lo</semantics> DFT code with the highly optimized SIRIUS multi-functional DFT package. This simplest realization of the separation of concerns approach yields substantial performance over the base EP code via additional task parallelism without significant change in the EP source code or user interface. We provide benchmarks of the interfaced code against the original EP using small bulk systems, and demonstrate performance on a spin-crossover molecule and magnetic molecule that are of size and complexity at the margins of the capability of the EP code itself.